A Production Calendar Based on Water Temperature, Spat Size, and Husbandry Practices Reduce OsHV-1 μvar Impact on Cultured Pacific Oyster Crassostrea gigas in the Ebro Delta (Catalonia), Mediterranean Coast of Spain - Carrasco, Noèlia; Gairin, Ignasi; Pérez, Josu; Andree, Karl B.; Roque, Ana; Fernández-Tejedor, Margarita; Rodgers, Chris J.; Aguilera, Cristobal; Furones, M. Dolors (Frontiers in Physiology, 2017)
Since 2006, the production of Pacific oyster Crassostrea gigas in the Ebro Delta area has dramatically declined from around 800 metric tonnes (MT) per year to 138 MT in 2011. This decline in production has had a significant socio-economic impact in a region where the shellfish sector is a traditional economic activity for many families. The identified agent responsible for this reduction in C. gigas production was Ostreid Herpesvirus microvar (OsHV- 1 µvar), which has been associated with C. gigas spat mortalities in France, and in many other countries. In Spain the episodes of mortality became critical for the regional shellfish production between 2008 until 2014, with mortality percentage up to 100%. In this study, local hatchery C. gigas spat was used as sentinel animals for epidemiological studies and management tests carried out with the aim of reducing oyster mortality in the Ebro Delta area. A production calendar mainly based on water temperature dynamics was designed around an optimal schedule for spat immersion. The immersion calendar included two optimal periods for spat immersion, in summer when temperatures are ≥ 25 °C and at the end of autumn and beginning of winter when they are ≤13 °C. Such production planning has reduced mortalities from 80% (in 2014 and previous years) to 2-7.5% in 2015 in cemented oysters. Furthermore, other recommendations related to spat immersion size, culture density and methodology, and cementing calendar, which helped to achieve the results, presented, were also recorded and transferred to local producers. This work presents a successfully tested management strategy reducing OsHV-1 µvar impact by designing new field management practices mainly focused on the handling and timing of spat immersion. This approach could be used as a management model in areas presenting similar production practices and environmental characteristics.